Evaluating the Strategy of Diskominfostandi Mahakam Ulu in Bridging the Digital Divide in Border Areas: A Study of Telecommunications Policy in Indonesia's 3T Regions - Andri Gunawan; Muhammad Noor; Adam Idris; Niken Nurmiyati (Golden Ratio of Social Science and Education, 2026)
This study examines the policy strategies implemented by the Communications, Informatics, Statistics, and Cryptography Agency (Diskominfostandi) of Mahakam Ulu Regency in addressing the digital divide and promoting equitable access to telecommunications and internet services in border regions. As one of Indonesia’s frontier, outermost, and underdeveloped (3T) regions, Mahakam Ulu faces persistent challenges related to geographical isolation, limited infrastructure, and unequal digital connectivity. Employing a descriptive qualitative approach, this study collected data through in-depth interviews with seven key informants, field observations, and document analysis conducted between March and April 2026. Data were analyzed thematically to identify policy strategies, implementation patterns, and institutional challenges in telecommunications governance. The findings reveal that significant disparities in digital connectivity persist across the region. Of the 49 BTS towers available, 15 (30.6%) remain inactive, while 35 of 50 villages continue to depend on satellite-based V-Sat connectivity. Diskominfostandi’s policy strategy is structured around three key dimensions: collaborative infrastructure development, digital human resource capacity building, and regulatory governance strengthening. However, policy implementation remains constrained by systemic challenges, including fragmented intergovernmental coordination, dependence on the central government agency BAKTI, a regional funding gap exceeding IDR 70 billion, and limited institutional capacity. This study contributes to the growing literature on digital divide reduction, telecommunications governance, and place-based digital policy by demonstrating that standardized national approaches are insufficient to address the unique conditions of 3T border regions. The study recommends an integrated policy model combining Low Earth Orbit (LEO) satellite technology, strengthened inter-agency coordination mechanisms, and community-centered digital empowerment programs to achieve sustainable digital inclusion and equitable regional development.